EVALUATION OF HALAL TOURISM DEVELOPMENT STRATEGY IN WEST NUSA TENGGARA PROVINCE (STUDY AT TOURISM DEPARTMENT) - Gaston Otto Malindir; Zainul Rahman (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2023)
The problems in the field show that efforts to develop the halal tourism market continue to be massive in Indonesia, but basically standard standards have not been laid down regarding the regulation of the halal concept for various existing tourist destinations, whether restaurants, saunas, spas, inns, airlines, travel agencies or other. On the other hand, there is a sense of public skepticism regarding the concept of halal tourism which is considered unable to guarantee the marginalized as well as with regard to the tools of identity politics. This study aims to find out how the halal tourism development strategy in West Nusa Tenggara Province is implemented. This research uses a qualitative method with a descriptive approach. The data collection technique used was literature study and field study which included observation, interviews and documentation. The data collection technique used is through data reduction, data presentation and drawing conclusions. The results of this study indicate that in the process of implementing halal tourism policies in West Nusa Tenggara Province, there are several obstacles that have implications for the lack of maximum implementation of these policies. Some of these obstacles are as follows: 1) Polemic on halal tourism policies in society, 2) reduced outreach and branding activities, finally 3) natural disasters and the Covid-19 pandemic. Based on the studies undertaken in the evaluation of the West Nusa Tenggara halal tourism program, it can be concluded that the program launched has not been able to fully achieve the initial target or vision. Therefore, innovation and evaluation are needed to correct some of the weaknesses in the implementation of the West Nusa Tenggara halal tourism program in the future. Key words; Evaluation, Development Strategy, Halal Tourism